The Effect of Educational Podcasts on Increasing Understanding of Concepts Among Students - Budi Nugroho; Wolnough Cale; Lie Jie (Yayasan Adra Karima Hubbi, 2024)
The rapid evolution of digital media has introduced various educational tools, among which educational podcasts have gained popularity. Podcasts offer an innovative and flexible method for students to engage with content outside traditional classroom settings. Despite their potential, there is limited empirical research on the effectiveness of educational podcasts in enhancing students’ understanding of concepts. This study aims to evaluate the impact of educational podcasts on students’ comprehension of academic concepts. Specifically, it investigates whether regular podcast exposure improves students’ conceptual understanding compared to traditional instructional methods. A quasi-experimental design involving 120 students from various educational levels was employed. Participants were divided into two groups: the experimental group, which used educational podcasts as supplementary material, and the control group, which continued with conventional teaching methods. Pre-tests and post-tests were administered to assess conceptual understanding before and after the intervention. Data analysis was conducted using quantitative methods, including t-tests and ANOVA. The results indicated a significant improvement in the experimental group’s conceptual understanding compared to the control group. The average score increase for the experimental group was 20% higher than that of the control group, suggesting that educational podcasts positively affect learning outcomes. Educational podcasts can effectively enhance students’ understanding of academic concepts. They provide an engaging and accessible way for students to reinforce learning outside classroom hours. The study highlights the potential of integrating podcasts into educational practices to support and improve student learning.